PHYSICAL FACILITIES AND INTERNAL EFFICIENCY OF PUBLIC UNIVERSITIES IN EDO AND DELTA STATES - Idehen, Kate Ogheneruna; Edeki, Oghomwen M. (African Journal of Educational Management, 2022)
The purpose of the study was to investigate physical facilities and internal efficiency of public universities in Edo and Delta States. Four research questions were raised that guided the study, descriptive survey research design of the ex-post-facto type was adopted, the population comprised all the four public universities in Edo and Delta States. Two universities were sampled, purposive random sampling was used to select the programmes from faculties of humanities and sciences. The instrument was two checklist titled Physical Facilities Checklist (PFC) and Student Enrolment and Flow Checklist (SEFC). Data were analysed with the use of descriptive statistics and reconstructed cohort method was used to compute the internal efficiency. Findings revealed that physical facilities were available but not adequate therefore not in tandem with NUC’s benchmark. Edo and Delta States Public Universities were internally inefficient with wastage ratio of 1:32. The study recommended that physical facilities should be made available and should be in tandem with NUC’s benchmark. Also, internal efficiency of these universities should be improved and maintained because wastage ratio of 1:32 was not technically good.